2017
DOI: 10.1108/jabs-10-2015-0183
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge sharing capability in healthcare organizations

Abstract: Purpose The purpose of this study is to examine the effect of organizational culture and stakeholders’ expectations on the relationship between organizational factors and organizations’ knowledge-sharing capability. Design/methodology/approach The data were collected from public and private hospital administrators in Thailand via a questionnaire. To test the hypotheses, the data were analyzed using regression analysis. Findings The results reveal that organizational culture has a positive effect on the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 64 publications
(83 reference statements)
0
4
0
Order By: Relevance
“…The quality of research kits is verified through validity and reliability tests (Kokanuch & Tuntrabundit, 2017). The conduct of validity test aims to evaluate how effective the mechanism being built can quantify the term to be tested (Sekaran & Bougie, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The quality of research kits is verified through validity and reliability tests (Kokanuch & Tuntrabundit, 2017). The conduct of validity test aims to evaluate how effective the mechanism being built can quantify the term to be tested (Sekaran & Bougie, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Sun et al (2021) explored the impact of organizational decentralization on job satisfaction and job performance, highlighting the importance of organizational structure in knowledge sharing. Kokanuch & Tuntrabundit (2017) found that decentralized organizational structures promote knowledge exchange among employees, emphasizing the role of structure in facilitating collaboration. Additionally, Walczak (2005) emphasized the importance of flexible organizational structures to encourage knowledge sharing and collaboration across traditional boundaries.…”
Section: The Effect Of Decentralized Organizational Structure On Coll...mentioning
confidence: 99%
“…T. Nguyen, and Phong, B.L., 2018). When the employees share the knowledge, the transfer produces value for the organization (Sveiby, 2001in Tuntrabundit, A.K.K., 2017. Knowledge sharing needs a social interaction that combines the exchange of employee's knowledge (know-how), skills, and experiences in the organization (Lin, 2007in Ali et al, 2019.…”
Section: The Effect Of Knowledge Sharing and Job Performancementioning
confidence: 99%